2004
DOI: 10.1002/tox.20025
|View full text |Cite
|
Sign up to set email alerts
|

Elemental sulfur: Toxicityin vivoandin vitroto bacterial luciferase,in vitroyeast alcohol dehydrogenase, and bovine liver catalase

Abstract: The aim of this research was to analyze the effects and the modes of action of elemental sulfur (S(0)) in bioluminescence and respiration of Vibrio fischeri cells and the enzymes crude luciferase, pure catalase, and alcohol dehydrogenase (ADH). Metallic copper removed sulfur and reduced the toxicity of acetone extracts of sediment samples analyzed in the bioluminescence test. The sulfur inhibition of cell bioluminescence was noncompetitive with decanal, the luciferase substrate; reversible, with maximum toxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…6). Elemental sulfur, S 8 , is capable of disrupting enzyme function (Cetkauskaite et al, 2004). Therefore, it would be possible that S 8 was the actual toxic agent in the upper water column in October 1997.…”
Section: Seasonal Behavior Of Rss Tnvmentioning
confidence: 99%
“…6). Elemental sulfur, S 8 , is capable of disrupting enzyme function (Cetkauskaite et al, 2004). Therefore, it would be possible that S 8 was the actual toxic agent in the upper water column in October 1997.…”
Section: Seasonal Behavior Of Rss Tnvmentioning
confidence: 99%
“…Large doses may have hepatotoxic properties. Rarerly sulphide absorbed from the intestine may produce the enterogenous cyanosis due to the formation of sulphaemoglobin [34][35] .…”
Section: Toxicitymentioning
confidence: 99%
“…against the toxicity of S 0 in vivo by an excess of the substrate, decanal (which is known to bind in the hydrophobic region of luciferase [13,17]); and 3) that the redox state of the enzyme in vitro (low concentrations of hydrogen peroxide and 2,4dithio-DL-threitol [DTT]) reversed the toxic effects of S 0 (16). It was deduced that S 0 acted as a reversible modifier, rather than an inhibitor, in V. fischeri cells, and did not compete with the natural substrate, decanal.…”
Section: Environmental and Synthetic Sulphydryl Group Inhibitors: Effmentioning
confidence: 99%
“…Data from previous research (16) on the mode of action of S 0 in V. fischeri in vivo and in vitro showed that: 1) the inhibition of bioluminescence by S 0 was reversible during exposures of up to 2 hours; 2) bioluminescence was not protected…”
Section: Introductionmentioning
confidence: 97%